2013
DOI: 10.1093/nar/gkt310
|View full text |Cite
|
Sign up to set email alerts
|

De novo piRNA cluster formation in the Drosophila germ line triggered by transgenes containing a transcribed transposon fragment

Abstract: PIWI-interacting RNAs (piRNAs) provide defence against transposable element (TE) expansion in the germ line of metazoans. piRNAs are processed from the transcripts encoded by specialized heterochromatic clusters enriched in damaged copies of transposons. How these regions are recognized as a source of piRNAs is still elusive. The aim of this study is to determine how transgenes that contain a fragment of the Long Interspersed Nuclear Elements (LINE)-like I transposon lead to an acquired TE resistance in Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 41 publications
6
102
0
Order By: Relevance
“…A spreading process for piRNA production was also observed for the flamenco piRNA-producing locus, which functions in the somatic follicle cells that surround germline cysts (Muerdter et al 2011). Further, analysis of previously established transgenic lines that carry an I-fragment within a P-transgene have shown that piRNA production capacity can spread within transgenes (Olovnikov et al 2013). The capacity to produce piRNAs invaded the whole I-derived transgene and reached in some cases flanking sequences.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…A spreading process for piRNA production was also observed for the flamenco piRNA-producing locus, which functions in the somatic follicle cells that surround germline cysts (Muerdter et al 2011). Further, analysis of previously established transgenic lines that carry an I-fragment within a P-transgene have shown that piRNA production capacity can spread within transgenes (Olovnikov et al 2013). The capacity to produce piRNAs invaded the whole I-derived transgene and reached in some cases flanking sequences.…”
Section: Discussionmentioning
confidence: 81%
“…Figure 3C shows that, as early as generation 3, the three types of G 0 maternal inheritance resulted in strong production of small RNAs covering the entire BX2 P{lacW} transgene length. Thus, partially homologous paramutations are associated with rapid and stable spreading of piRNA production by nonhomologous sequences of the targets, similarly to what was found for target transgenes (Muerdter et al 2011;Olovnikov et al 2013;Han et al 2015;Mohn et al 2015) or transposable elements (Shpiz et al 2014).Further, the paramutagenicity of P-1152 BX2*, RS3 BX2*, and P-1152+RS3 BX2* females was tested. Figure 4 shows that maternal transmission of cytoplasm produced by these females, combined to paternal transmission of a BX2 naive locus, resulted in female progeny showing strong trans-silencing properties.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…For a genomic region of interest, the presence of homologous piRNAs in the ooplasm is associated with the deposition of H3K9me3 and the onset of piRNA production (Olovnikov et al 2013;Le Thomas et al 2014a,b;Shpiz et al 2014). Experiments in which tandemly-duplicated arrays of transgenes were epimutated into piRNA clusters suggest that higher-copy arrays are both more likely to undergo epimutation, and more likely to stably maintain piRNA production over successive generations after they have been epimutated, rather than spontaneously reverting to the quiescent state (de Vanssay et al 2012).…”
Section: Mutation and Selection In The Rapid Evolution Of Host Represmentioning
confidence: 99%